Il centrosinistra italiano alla prova delle primarie 2012. Bersani, Renzi e Vendola: modelli di leadership a confronto - Damiani, Marco (SocietàMutamentoPolitica, 2013)
This work analyzes the different models of leadership observed in the Italian centre-left coalition during the primary election of 2012th. In details, the paper discusses the different roles of leadership played by Pierluigi Bersani, Matteo Renzi and Nichi Vendola.